A comparison of morning priming exercise using traditional-set and cluster-set configurations on afternoon explosive performance - Zhe Wang; Bing Yan; Yang Wang; Conghui Zhang; Feng Chen; Olivier Girard (Termedia Publishing House, 2024)
The impact of two priming exercise protocols using traditional (TS) or cluster-set (CS) arrangements on explosive performance 6 hours later were examined. Sixteen male collegiate athletes performed three testing sessions (one baseline without any prior exercise in the morning and two experimental sessions) separated by 72 hours. Participants completed two morning (9-11 am) priming protocols in a randomized order, either using a TS (no rest between repetitions) or CS (30 seconds of rest between repetitions) configuration. The protocols consisted of 3 sets×3 repetitions of barbell back squat at 85% of 1 repetition maximum, with 4 minutes of rest between sets. In the afternoon (3-5 pm) of each trial, after a 6-hour rest period, a physical test battery was conducted that replicated baseline testing, including countermovement jump, 20-meter straight-line sprint, and T-test abilities. Across both conditions, participants exhibited increased countermovement jump height, 20-meter sprint time and T-test time compared to baseline (P < 0.05). Improvements in countermovement jump height (+4.4 ± 5.4%; P = 0.008) and 20-meter sprint time (+1.3±1.7%; P = 0.022), but not T-test time (+1.1±3.3%; P = 0.585), were significantly greater for CS than TS. In conclusion, compared to a traditional set arrangement, a morning-based priming protocol using a cluster-set configuration led to superior explosive performance benefits in the afternoon.